Orf virus DNA prime-protein boost strategy is superior to adenovirus-based vaccination in mice and sheep - Wang, Yan; Sun, Shihui; Zhao, Kui; Du, Le; Wang, Xinyue; He, Wenqi; Gao, Feng; Song, Deguang; Guan, Jiyu (Frontiers in Immunology, 2023)
Contagious ecthyma (Orf), an acute and highly contagious zoonosis, is prevalent worldwide. Orf is caused by Orf virus (ORFV), which mainly infects sheep/goats and humans. Therefore, effective and safe vaccination strategies for Orf prevention are needed. Although immunization with single-type Orf vaccines has been tested, heterologous prime-boost strategies still need to be studied. In the present study, ORFV B2L and F1L were selected as immunogens, based on which DNA, subunit and adenovirus vaccine candidates were generated. Of note, heterologous immunization strategies using DNA prime-protein boost and DNA prime-adenovirus boost in mice were performed, with single-type vaccines as controls. We have found that the DNA prime-protein boost strategy induces stronger humoral and cellular immune responses than DNA prime-adenovirus boost strategy in mice, which was confirmed by the changes in specific antibodies, lymphocyte proliferation and cytokine expression. Importantly, this observation was also confirmed when these heterologous immunization strategies were performed in sheep. In summary, by comparing the two immune strategies, we found that DNA prime-protein boost strategy can induce a better immune response, which provides a new attempt for exploring Orf immunization strategy.